2021
DOI: 10.1055/s-0040-1716632
|View full text |Cite
|
Sign up to set email alerts
|

1-Year Evaluation of OT Bridge Abutments for Immediately Loaded Maxillary Fixed Restorations: A Multicenter Study

Abstract: Objective  Preliminary data on survival and success rates of immediately loaded, maxillary, screw-retained, implant-supported, fixed restorations delivered on narrow and low-profile OT Equator abutments (OT Bridge, Rhein’83) were evaluated. Materials and Methods This retrospective study evaluated data collected from patients rehabilitated with OT Bridge prosthetic concept between November 2017 and February 2019 in six different centers. Outcome measures were implant and prosthetic survival rates, biological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Exceptionally, clinicians can place deep the implants up to 1.5 to 2 mm in case of postextractive implants and very thin biotype. In these cases, one abutment at the one time concept 36 37 or tissue-level implants should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Exceptionally, clinicians can place deep the implants up to 1.5 to 2 mm in case of postextractive implants and very thin biotype. In these cases, one abutment at the one time concept 36 37 or tissue-level implants should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Only few works have been carried on this system out, and research and predictable protocols are only at the beginning, but the clinical results seem to be promising. However, studies on the follow-up period and the number of cases reported with "all-on-four" rehabilitation using the OT bridge system are limited [22][23][24]. No studies have been proposed to evaluate the influence of removing one or two anterior screws in an "all-on-four" rehabilitation and the stability of this specific system after mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…A possible solution, retaining the benefits of a screw-in prosthesis, may be provided by the OT-Bridge system [16] in the absence of one or two anterior prosthetic screws [23,24]. In this way, the stability of the OT Bridge system is provided by both the posterior screws and the interlocking system between the acetal Seeger, inserted in the extragrade abutment, and the subequatorial region of the OT equator attachments in the anterior region.…”
Section: Introductionmentioning
confidence: 99%
“…The so called "Exit Strategy" allows to move from a removable to fixed denture, limiting the biologic and economic impact for the patients. In this way, the OT Equator attachments can work both as an attachment system and as an intermediate abutment for fixed restorations [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%